Study on Image Classification Method Based on Small Sample Learning - Wang, Dongxue (Bright Publisher, 2022)
Image classification as according to their different features of reflected in the image information, make a distinction between different categories of target image processing methods, and especially for quantitative analysis using the computer, each of the images or image pixels, or regional planning is one of the several categories, in lieu of visual interpretation of the person, It has important practical value for the study of image classification method. However, the current study of image classification method based on small sample learning cannot effectively follow the development needs of society and industry, so it is urgent to carry out effective reform. Based on this, this paper first analyzes the problems existing in the research system construction of image classification method in small sample learning, and then gives the construction strategy of image classification method system according to these problems.